Lenvatinib Plus Pembrolizumab vs. Chemotherapy in Pretreated Patients With Advanced Endometrial Cancer: A Cost-Effectiveness Analysis - Feng, Mingyang; Chen, Yue; Yang, Yang; Li, Qiu (Frontiers in Public Health, 2022)
Background: In the international, randomized, open-label, phase 3 study 309-KEYNOTE-775 trial, lenvatinib plus pembrolizumab (LP) showed improved progression-free survival (PFS), and overall survival (OS) compared with chemotherapy in pretreated patients with advanced endometrial cancer. This study aimed to investigate whether LP is cost-effective compared with chemotherapy. Materials and methods: The clinical data for this model was derived from the 309-KEYNOTE-775 trial. Costs and utility were either derived from the standard fee database or extracted from previously published literature. A three-state Markov model was developed to simulate the disease process of patients with advanced endometrial cancer. One-way sensitivity analyses were conducted to investigate the impact of variables in the analysis model. Probabilistic sensitivity analysis was performed based on 10,000 Monte-Carlo simulations. A subgroup analysis was performed to test whether LP is cost-effective in mismatch repair–proficient (pMMR) patients. Results: LP provided an incremental 0.64 Quality-adjusted life years (QALYs) with an incremental cost of $241,278.18, compared with chemotherapy, resulting in the incremental cost-effectiveness ratio (ICER) of $378,251.44/QALY, which exceeded the willingness to pay (WTP) threshold. While in the pMMR subgroup, the ICER increased to $413,256.68/QALY. The variance of the utility of PFS state, costs of LP, and utility of progressive disease state were the most influential factors in the sensitivity analysis. Conclusion: Under the current WTP threshold, LP is not cost-effective compared with chemotherapy in pretreated patients with advanced endometrial cancer.